A Comparative Analysis of Tunneling FET Characteristics for Low Power Digital Circuits (International Journal of Current Engineering and Technology, 2014)
The technology used in today’s transistors is called “field effect” whereby voltage induces an electron channel that activates the transistor. But field effect technology is approaching its limits, particularly in terms of power consumption. With the rapid increase of the number of circuits on a chip, power consumption has increased and appeared as the leading design challenge. In order to achieve significantly reduced power consumption, the transistor operating voltage needs to be reduced. However; the reduction in power consumption of the MOSFETs used in today’s electronic circuits is reaching the fundamental limit. However, the reduction in power consumption of the MOSFETs used in today’s electronic circuits is reaching the fundamental limit. This review introduces and summarizes progress in the development of the tunnel field-effect transistors (TFETs) including its origin, current experimental and theoretical performance relative to the metal–oxide–semiconductor field-effect transistor (MOSFET), design tradeoffs, and fundamental challenges.
Keywords: TFETs, subthreshold swing, band to band tunneling, ION/IOFF ratio.